An outdoor hotel quarantine facility model in Australia: best practice with optimal outcomes - Stephanie J. Curtis; Abigail Trewin; Kathleen McDermott; Karen Were; Tracy Walczynski; Len Notaras; Nick Walsh (Elsevier, 2022)
Abstract Objective: To describe the operationalisation of a novel outdoor quarantine facility managed by the Australian Medical Assistance Team, the Howard Springs International Quarantine Facility (HSIQF) at the Centre for National Resilience in the Northern Territory, Australia. Methods: We collated documentation and data from HSIQF to describe policies and procedures implemented and performed a descriptive analysis of key procedures and outcomes. Results: From 23 October 2020 to 31 March 2021, 2.2% (129/5,987) of residents were confirmed COVD‐19 cases. On average per day, 82 [Interquartile Range (IQR): 29‐95] staff completed personal protective equipment (PPE) training, 94 [IQR: 90‐104] staff completed antigen testing and 51 [IQR: 32‐136] staff completed polymerase chain reaction testing. The operation focused on building a safe environment with infection prevention and control adherence and workforce sustainability. There was no leakage of SARS‐CoV‐2 to staff or the community and no PPE compromises requiring staff to quarantine for 14 days. Conclusion: HSIQF demonstrates the operationalisation of an effective, safe and replicable quarantine system. Implications for public health: Quarantine is a critical public health tool for pandemic control. The HSIQF operations may be useful to inform the establishment and management of quarantine facilities for future and current disease outbreaks.